Necessidades formativas da pós-modernidade e a formação contínua de professores de Ciências - Maia, Dayse Peixoto (2015)
This paper analyzes the training needs of science teachers through the psychosocial dimension in its relations with the identity, culture and lifelong learning in the context of post-modernity. For its development we seek the elaboration of some theorists that argue about changes of the characteristics of postmodernity, including Bauman (2014, 2013th, b, c, 2009, 2005, 2002, 2001), Hall (2014), Lipovetsky (2014, 2013 2012, 2009, 2007, 2005), Giroux (2011) and Hargreaves (2005, 2003, 2002), which helped us to discuss the cultural and social changes experienced in the context of formal schooling. Dialogued with the propositions of Milk and Yamashiro (2013), Ramos (2013), Galindo (2011) and other Brazilian authors to contextualize to our reality, interferences in teaching and their coping possibilities through continuous training.The research was developed from the phenomenological qualitative approach used observing techniques, questionnaires and group discussions, involving twenty science teachers from four schools of public schools in the city of Manaus. We proposed the thesis that the meeting the training needs of science teachers, through interventions aimed at continuous training through the psychosocial approach is constituted as a pledge condition for the development of identity and professionalization. The analysis on the data obtained was empirical and interpretative nature. The results showed that the identity and teaching culture are in the process of adapting to new socio-cultural conditions posed by postmodernity and the continuous development processes in models made by education departments has not met its formative function by being distanced from the context subjective featuring the new conditions of life and professional development. It reformulate the training proposal expanding access to masters and doctoral degrees in the field of Teaching and Education, as well as the reformulation of proposals for continuing education within public schools to a more appropriate care to psychosocial training demands of teachers, resulting from cultural developments of postmodernity.